Sensitivity of low-degree solar p modes to active and ephemeral regions: frequency shifts back to the Maunder minimum. (29th August 2019) - Chaplin, William J; Howe, Rachel; Basu, Sarbani; Elsworth, Yvonne; Milbourne, Timothy W; Haywood, Raphaëlle D; Davies, Guy R; Hale, Steven J; Miglio, Andrea; Ross, Eddie
ABSTRACT: We explore the sensitivity of the frequencies of low-degree solar p modes to near-surface magnetic flux on different spatial scales and strengths, specifically to active regions with strong magnetic fields and ephemeral regions with weak magnetic fields. We also use model reconstructions from the literature to calculate average frequency offsets back to the end of the Maunder minimum. We find that the p-mode frequencies are at least 3 times less sensitive (at 95 per cent confidence) to the ephemeral-region field than they are to the active-region field. Frequency shifts between activity cycle minima and maxima are controlled predominantly by the change of active region flux. Frequency shifts at cycle minima (with respect to a magnetically quiet Sun) are determined largely by the ephemeral flux, and are estimated to have been $0.1\, \rm μ Hz$ or less over the last few minima. We conclude that at epochs of cycle minimum, frequency shifts due to near-surface magnetic activity are negligible compared to the offsets between observed and model frequencies that arise from inaccurate modelling of the near-surface layers (the so-called surface term). The implication is that this will be the case for other Sun-like stars with similar activity, which has implications for asteroseismic modelling of stars.